2010
DOI: 10.1155/2011/309390
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effects of Cagaita (Eugenia dysenterica, DC.) Leaf Extracts on Diarrhea Treatment

Abstract: Eugenia dysenterica is a plant typically found in the Cerrado biome and commonly used in popular medicine due to its pharmacological properties, which include antidiarrheal, skin healing, and antimicrobial activities. The effects of ethanolic extract, aqueous extract and infusion of E. dysenterica leaves on intestinal motility and antidiarrheal activity were evaluated using ricin oil-induced diarrhea in rats. At doses of 400 and 800 mg·Kg−1, the ethanolic extract decreased intestinal motility while the other e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 53 publications
(59 reference statements)
2
17
0
8
Order By: Relevance
“…Additional, EDE also reduced renal and liver histopathological damage caused by Cr(VI), although areas with hydropic degeneration could still be seen in the liver. However, it was a reversible alteration possibly generated by the extract, as already reported by Lima et al (2011).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Additional, EDE also reduced renal and liver histopathological damage caused by Cr(VI), although areas with hydropic degeneration could still be seen in the liver. However, it was a reversible alteration possibly generated by the extract, as already reported by Lima et al (2011).…”
Section: Discussionsupporting
confidence: 66%
“…(Myrtaceae), popularly known as cagaita or cagaiteira, is a polyphenol rich-plant from the Cerrado, a Brazilian savannah biome (Almeida et al 1998). As a medicine, the leaves are traditionally used for the treatment of diarrhoea and dysentery but, in contrast, the fruits have laxative property (Almeida et al 1998;Lima et al 2010Lima et al , 2011. As a food, the cagaita fruit has a high pulp yield with reduced energy value and is a source of folates, carotenoids, vitamins A and C (Cardoso et al 2011), quercetin, kaempferol and acid ellagic (Gonçalves et al 2010).…”
mentioning
confidence: 99%
“…Serial dilutions of the homogenates were plated in triplicate on mannitol salt agar (Himedia, India), and the results were expressed as CFU g Ϫ1 of tissue (17,24). The other half of the wounded tissue was stored for histological analysis as described previously by Lima and coworkers (25).…”
mentioning
confidence: 99%
“…The cagaita fruit is a yellow-orange roughly spherical berry with a diameter of approximately 3-4 cm and mass varying between 15 and 37 g that has a sweet-sour and slightly astringent taste (Cardoso, Martino, Moreira, Ribeiro, & Pinheiro-Sant'Ana, 2011;Clovegarden, 2015). The cagaita fruit is used in various regional preparations, such as jams, ice-cream, liqueurs, and juices; whereas both the fruit and the leaves are used as popular alternative medicine by local communities to treat diarrhea, diabetes, and jaundice (Lima et al, 2011). Cagaita is considered to be a source of vitamin C and phenolic compounds, including quercetin, ellagitannins, ellagic acid, and kaempferol (Cardoso et al, 2011;Gonçalves, Lajolo, & Genovese, 2010), which were previously shown to exert important biological functions preventing the development of obesity and type 2 diabetes (Del Rio, Borges, & Crozier, 2010;Scalbert et al, 2005).…”
Section: Introductionmentioning
confidence: 99%